Tumor characteristics and surgical outcome in incidentally discovered pheochromocytomas and paragangliomas - Xinlei Chen (Endocrine Connections, 2018)
Objective: The proportion of incidentally discovered pheochromocytomas and paragangliomas (PPGL) has increased over time. However, our knowledge of them is quite limited. The purpose of this retrospective study is to generalize the commonalities in incidentally discovered PPGL, offer evidence for clinical diagnosis and management. Methods: Five hundred twenty-six patients were included in our study after filtration from the database of West China Hospital of Sichuan University between May, 2007 and December, 2016. Among the patients, 148 of them were incidental findings and 378 of them were suspected findings. All patients’ demography and tumor characteristics were recorded in detail, especially hemodynamic records and hormonal assays. The reasons for taking radiography were also collected. Most patients received preoperative medical preparation. Intraoperative and postoperative courses as well as surgical outcomes were also analyzed to identify differences between incidental findings and suspected findings. Results: Incidentally discovered PPGL took up 28.1% of the study population. Suspected PPGLs had a higher prevalence of hypertension, lower proportion of non-functioning PPGL, higher prevalence of MEN2 and better post-surgical blood pressure recovery than incidental finding group. However, patients in the incidental finding group showed no significant difference in preoperative blood pressure and hormonal assays with suspected findings in metaphrine and normetaphrine in plasma and urine (P > 0.05). Conclusions: Due to the development of technology, more PPGLs are discovered incidentally. Considering the tumor characteristics and surgical outcome, surgical decisions should be made more cautiously.